Amphetamine withdrawal differentially affects hippocampal and peripheral corticosterone levels in response to stress - Bray, Brenna (Brain Res, 2016)
Amphetamine withdrawal is associated with heightened anxiety-like behavior, which is directly driven by blunted stress-induced glucocorticoid receptor-dependent serotonin release in the ventral hippo-campus. This suggests that glucocorticoid availability in the ventral hippocampus during stress may be reduced during amphetamine withdrawal. Therefore, we tested whether amphetamine withdrawal alters either peripheral or hippocampal corticosterone stress responses. Adult male rats received amphetamine (2.5 mg/kg, ip) or saline for 14 days followed by 2 weeks of withdrawal. Contrary to our prediction, microdialysis samples from freely-moving rats revealed that restraint stress-induced corticosterone levels in the ventral hippocampus are enhanced by amphetamine withdrawal relative to controls. In separate groups of rats, plasma corticosterone levels increased immediately after 20 min of restraint and decreased to below stress-naïve levels after 1 h, indicating negative feedback regulation of corticosterone following stress. However, plasma corticosterone responses were similar in amphetamine-withdrawn and control rats. Neither amphetamine nor stress exposure significantly altered protein expression or enzyme activity of the steroidogenic enzymes 11β-hydroxysteroid dehydrogenase (11β-HSD1) or hexose-6-phosphate dehydrogenase (H6PD) in the ventral hippocampus. Our findings demonstrate for the first time that amphetamine withdrawal potentiates stress-induced corticosterone in the ventral hippo-campus, which may contribute to increased behavioral stress sensitivity previously observed during amphetamine withdrawal. However, this is not mediated by either changes in plasma corticosterone or hippocampal steroidogenic enzymes. Establishing enhanced ventral hippocampal corticosterone as a direct cause of greater stress sensitivity may identify the glucocorticoid system as a novel target for treating behavioral symptoms of amphetamine withdrawal.